2018
DOI: 10.1021/acschemneuro.8b00322
|View full text |Cite
|
Sign up to set email alerts
|

Excitation-Energy-Dependent Molecular Beacon Detects Early Stage Neurotoxic Aβ Aggregates in the Presence of Cortical Neurons

Abstract: energy-dependent molecular beacon detects early stage neurotoxic A aggregates in the presence of cortical neurons. ACS β Chemical Neuroscience 10 (3) , pp.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Changes in protein structure are accompanied by a change in the equilibrium of conformational states. We have recently demonstrated that monitoring REES for mAbs labelled with an extrinsic fluorophore can report on relatively low- n changes in oligomeric state [ 36 ]. Similarly, the REES effect has been used to infer differently folded/aggregated states of proteins using singe-Trp containing examples [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in protein structure are accompanied by a change in the equilibrium of conformational states. We have recently demonstrated that monitoring REES for mAbs labelled with an extrinsic fluorophore can report on relatively low- n changes in oligomeric state [ 36 ]. Similarly, the REES effect has been used to infer differently folded/aggregated states of proteins using singe-Trp containing examples [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…More recently we have shown a similar detection sensitivity in multi-trp proteins, with the approach being able to discern differences in molecular flexibility, where the X-ray crystal structures are identical [ 35 ]. Similarly, we have recently shown that extrinsic fluorophore labelling or mAbs can be used to track changes in low- n oligomer formation [ 36 ]. We term our method of quantifying REES data, QUBES (quantitative understanding of bimolecular edge shift), in order to distinguish other treatments of REES data.…”
Section: Introductionmentioning
confidence: 99%
“…Eq 3) since it predicts a maximum magnitude of the CSM, corresponding to the fully relaxed state, (Figure 1C). Indeed, ourselves and others have observed saturation of the REES effect with non-Trp fluorophores used as molecular probes 18 or ligands, 19 and so Eq 7 is logical for the REES effect in proteins.…”
Section: Resultsmentioning
confidence: 99%
“…We have recently demonstrated that monitoring REES for mAbs labelled with an extrinsic fluorophore can report on relatively low-n changes in oligomeric state. 36 Similarly, the REES effect has been used to infer differently folded/aggregated states of proteins using singe-Trp containing examples. 30 Based on these findings and given the sensitive discrimination of mAbs by the QUBES data shown above, we wished to explore whether differences in multi-Trp REES data are sensitive to changes in protein structure in mAbs.…”
Section: Figures 3b and 3cmentioning
confidence: 99%
“…35 Similarly, we have recently shown that extrinsic fluorophore labelling or mAbs can be used to track changes in low-n oligomer formation. 36 We term our method of quantifying REES data, QUBES (quantitative understanding of bimolecular edge shift), in order to distinguish other treatments of REES data. Based on the apparent power and potential information content of the REES phenomenon, we reason that this approach could be developed further to deliver sensitive detection of changes in a proteins dynamic profile as well as overall conformation.…”
Section: Introductionmentioning
confidence: 99%